Atomic‐Scale CoOx Species in Metal–Organic Frameworks for Oxygen Evolution Reaction. (3rd August 2017) - Dou, Shuo; Dong, Chung‐Li; Hu, Zhe; Huang, Yu‐Cheng; Chen, Jeng‐lung; Tao, Li; Yan, Dafeng; Chen, Dawei; Shen, Shaohua; Chou, Shulei; Wang, Shuangyin
Abstract : The activity of electrocatalysts strongly depends on the number of active sites, which can be increased by downsizing electrocatalysts. Single‐atom catalysts have attracted special attention due to atomic‐scale active sites. However, it is a huge challenge to obtain atomic‐scale CoO x catalysts. The Co‐based metal–organic frameworks (MOFs) own atomically dispersed Co ions, which motivates to design a possible pathway to partially on‐site transform these Co ions to active atomic‐scale CoO x species, while reserving the highly porous features of MOFs. In this work, for the first time, the targeted on‐site formation of atomic‐scale CoO x species is realized in ZIF‐67 by O2 plasma. The abundant pores in ZIF‐67 provide channels for O2 plasma to activate the Co ions in MOFs to on‐site produce atomic‐scale CoO x species, which act as the active sites to catalyze the oxygen evolution reaction with an even better activity than RuO2 . Abstract : Through the efficient and mild O2 ‐plasma process, atomic‐scale CoO x species in a ZIF‐67 matrix are on‐site formed, which are in favor of combining with OH* to act as active sites to directly catalyze the oxygen evolution reduction with an even better activity than commercial RuO2 .